The Introduction of a Short-Term Earnings-Related Parental Leave Benefit System and Differential Effects on Employment Intentions - Bergemann, Annette; Riphahn, Regina Therese (Schmollers Jahrbuch, 2011)
German family policy underwent a reform in 2007, when the new instrument of "Elterngeld"replaced the previous "Erziehungsgeld". The transfer programs differ in various dimensions. We study the effects on the labor supply of young mothers, by comparing behavior before and after the reform. We separately consider women of high and low incomes, which were treated differently under the old "Erziehungsgeld"-regime, and differentiate the periods before and after the expiration of transfer receipt. Our results mainly confirm expectations based on a labor supply framewor
WiSo-Import:2015-03-26:933
Keywords: Transformation; parents money; fertility; female labor supply; child subsidy